1993
DOI: 10.1037/0735-7044.107.6.926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperglycemia on memory and hormone levels in dementia of the Alzheimer type: A longitudinal study.

Abstract: The effect of hyperglycemia on hormone levels, metabolite levels, and memory performance was examined in 22 subjects with very mild and mild probable dementia of the Alzheimer type (DAT) and in 12 normal elderly adults. Subjects were tested in 3 plasma glucose conditions (fasting baseline, 175 mg/dl, and 225 mg/dl) at initial and 18-month follow-up sessions. Initially, adults with very mild DAT showed memory facilitation and elevations in plasma insulin in the 225-mg/dl glucose condition relative to baseline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 51 publications
5
93
1
1
Order By: Relevance
“…Subjects were fasted in order to minimize the potential confound of varying glucose levels on NMDA receptor-related function and on direct measures of cognitive function (Izumi et al 1993;Craft et al 1993;Newcomer et al 1994a; Newcomer et al in press;Craft et al 1996). Ketamine (or 0.9% normal saline "placebo" solution) was infused intravenously at specified loading dose and maintenance infusion rates (see below) using a Harvard pump apparatus, while 0.9% normal saline was used to maintain a separate patent draw line.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were fasted in order to minimize the potential confound of varying glucose levels on NMDA receptor-related function and on direct measures of cognitive function (Izumi et al 1993;Craft et al 1993;Newcomer et al 1994a; Newcomer et al in press;Craft et al 1996). Ketamine (or 0.9% normal saline "placebo" solution) was infused intravenously at specified loading dose and maintenance infusion rates (see below) using a Harvard pump apparatus, while 0.9% normal saline was used to maintain a separate patent draw line.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, ketamine is known to produce increases in plasma cortisol (Krystal et al 1994;Fahringer et al 1974;Clarke et al 1974;Oyama et al 1970) and glucose (Kaniaris et al 1975;Clarke et al 1974), and this group has reported cognitive effects of glucose and insulin (Newcomer et al 1994a; Newcomer et al in press;Craft et al 1993;Craft et al 1996) and glucocorticoids (Newcomer et al 1994b) in humans, motivating the measurement of these variables to rule out confounds to the interpretation of cognitive effects. For similar reasons, plasma epinephrine and norepinephrine were measured with a single isotope derivative (radioenzymatic) method (Shah et al 1985).…”
Section: Plasma Assaysmentioning
confidence: 99%
“…At a subsequent follow-up 18 months following the original testing session, this same pattern of memory enhancement was observed for patients maintaining diagnostic criteria for very mild Alzheimer's disease. However, for those participants whose Alzheimer's dementia had progressed beyond the classification of 'very mild' over the 18-month interval between test phases, glucose facilitation of memory was no longer observed in either of the two glucose conditions (Craft et al, 1993).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…In a further study by the same group, cognitive performance was assessed in Alzheimer's patients under three conditions (fasting glucose, blood glucose concentration = 9.7 mmol/L and blood glucose concentration = 12.5 mmol/L), with a hyperglycaemic clamping procedure used to achieve target blood glucose concentrations (Craft et al, 1993). Verbal episodic memory performance was significantly enhanced following an increase in blood glucose to 12.5 mmol/L only, relative to performance following an overnight fast, for participants with very mild Alzheimer's dementia.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Delayed recall was divided by immediate recall to obtain a savings score or a percent of information retained. Reliability and validity of WMS-R and WMS-III Logical Memory, and this modified version are very good (Craft et al, 1992(Craft et al, , 1993(Craft et al, , 1994Wechsler, 1987Wechsler, , 1997b.…”
Section: Verbal Memorymentioning
confidence: 99%